The practice of feedback in learning through artful initiatives - Barroca, Ana; Neto, Catarina; Silveira, Ana (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The European education and training systems continue to fall short in providing the right skills for employability. The Feedback project is a European initiative, co-funded by the Erasmus + Programme, and counts with the participation of five organisations from four European countries to further understand, develop and deliver innovative learning resources about the practice of feedback, supported by arts-based learning initiatives.